Carcass characteristics of feedlot fattened northern and western Sudan zebu cattle - El-Shafie, S.A.; McLeroy, G.B. (1965)
The carcass characteristics of Sudanese cattle are investigated in relation to the improved marketing procedures. Results of initial use of meat laboratory involving a total of 31 head of fattened cattle from Western Baggara and Butana bulls were evaluated. Data on beef quality and slaughter by-products included. There is a possibility of producing high quality beef from these animals.